Magnon detection using a ferroic collinear multilayer spin valve - Cramer, Joel; Fuhrmann, Felix; Ritzmann, Ulrike; Gall, Vanessa; Niizeki, Tomohiko; Ramos, Rafael; Qiu, Zhiyong; Hou, Dazhi; Kikkawa, Takashi; Sinova, Jairo; Nowak, Ulrich; Saitoh, Eiji; et al. (Nature Communications, 2018)
Information transport and processing by pure magnonic spin currents in insulators is a promising alternative to conventional charge-current-driven spintronic devices. The absence of Joule heating and reduced spin wave damping in insulating ferromagnets have been suggested for implementing efficient logic devices. After the successful demonstration of a majority gate based on the superposition of spin waves, further components are required to perform complex logic operations. Here, we report on magnetization orientation-dependent spin current detection signals in collinear magnetic multilayers inspired by the functionality of a conventional spin valve. In Y 3 Fe 5 O 12 |CoO|Co, we find that the detection amplitude of spin currents emitted by ferromagnetic resonance spin pumping depends on the relative alignment of the Y 3 Fe 5 O 12 and Co magnetization. This yields a spin valve-like behavior with an amplitude change of 120% in our systems. We demonstrate the reliability of the effect and identify its origin by both temperature-dependent and power-dependent measurements.
CRIS-Team Scopus Importer:2023-03-27